1969
DOI: 10.3171/jns.1969.30.2.0165
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cure of Intracavernous Aneurysm of the Internal Carotid Artery in a 14-Month-Old Child

Abstract: HE incidence of intracranial aneurysms in the general population is estimated to be less than 2%. a,14,16 Aneurysms occurring below the age of 20 years are quite uncommon. 1-3 McDonald and Korb, 12 in their collected series of 1125 intracranial aneurysms, noted that the youngest patient was 1 89 years old. They had only 28 patients younger than 15 years of age. Similarly, Taveras and Wood 17 found only four cases of intracranial aneurysms in patients under 15 years of age at the New York Neurological Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

1974
1974
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…It is worth noting, however, that of the 7 cases in our review, in whom the parent artery thrombosed, in 6 (86%) thrombo sis occurred in the middle cerebral artery [10,11,18,22,27]. Other authors have discussed a similar tendency, attributing this to the narrowness of the feeding artery [ 15,28], Three of 7 of these cases (43%) received antifibri nolytic therapy [22. 27], This case also demonstrates a rare location for an aneu rysm.…”
Section: Discussionmentioning
confidence: 70%
“…It is worth noting, however, that of the 7 cases in our review, in whom the parent artery thrombosed, in 6 (86%) thrombo sis occurred in the middle cerebral artery [10,11,18,22,27]. Other authors have discussed a similar tendency, attributing this to the narrowness of the feeding artery [ 15,28], Three of 7 of these cases (43%) received antifibri nolytic therapy [22. 27], This case also demonstrates a rare location for an aneu rysm.…”
Section: Discussionmentioning
confidence: 70%
“…Barker (1954) reported a patient who, o n postmortem examination, was found to have bilateral mycotic internal carotid aneurysms in conjunction with thrombophlebitis of the cavernous sinus. Devadiga et al (1969) reported a 14-month-old infant who presented with fever of unknown etiology followed by left hemiparesis, chemosis and complete ophthalmoplegia of the left eye. The cerebrospinal fluid did not indicate purulent meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…According to most large series (Dandy 1969, du Boulay 1965, Lartinen 1964, Mc-Donald 1939 approximately 3 % of clinically apparent intracranial aneurysms occur in patients under 17 years of age. The occurrence of so-called giant aneurysms, which may simulate neoplasms in their mode of presentation (Money 1969), is far less common in this age group, but nevertheless, has been well-documented (Devadiga 1969, Jane 1961, Vapolohti 1969. The following case, that of a 13 year old girl, is of particular interest, however, because her progressive neurological deficit, which suggested an expanding lesion of the upper brain stem, was found to be due to a posteriorly directed, giant aneurysm arising from the internal carotid artery.…”
Section: Introductionmentioning
confidence: 99%